Renal pharmacy attachment @ UiTM immersive learning in action - Ibrahim, Norkasihan (Faculty of Pharmacy, 2025)
The Renal Pharmacy Attachment @ UiTM, held from 23rd June to 11th July 2025, was a highly impactful threeweek professional training programme for registered pharmacists, medical officers, and other healthcare providers interested in updating their knowledge and building competencies in renal pharmacotherapy. The intensive course combined online lectures and tutorials, as well as on-campus clerkship sessions at Hospital Al-Sultan Abdullah (HASA), UiTM. This joint initiative between the Faculty of Pharmacy and the Faculty of Medicine, UiTM, was spearheaded by Dr. Norkasihan Ibrahim, Dr. Muhammad Iqbal Abdul Hafidz, and Mr. Mohd Rahimi Muda, who brought together their expertise to deliver a transformative learning experience grounded in collaborative care.